Social Minorities and Heterogeneity: José Marti and the European Immigration (Anclajes, 2011)
The article analyzes Jose Marti's conceptions around the immigration phenomenon in the United States in the late 19th century, a central problem in the Western World at the time. It deals with Marti’s particular vision of social minorities and heterogeneity in his North American Scenes, specially those scenes centered in the labor world. It focuses on the last chronicle published in La Nación Buenos Aires newspaper -The Italians' Murder-, in which it is possible to notice the narrative, descriptive and argumentative strategies used by the journalist to report a xenophobic event. Likewise, this piece of work examines the complex integration of Chinese workers into the North American society and the kaleidoscope of images that the writer provides of the migratory group; such a vision is oriented to untie social and cultural prejudices. Marti's concerns around minorities in the United States are read in accordance with the heterogeneous social composition of Cuban context in the colonial framework at the turn of the century.
Keywords: José Martí; Escenas Norteamericanas; social minorities; european inmigration; chronicle